Experiment on transient thermodynamic behavior of a cryogenic storage tank protected by a composite insulation structure. (1st May 2023) - Yang, Yilun; Jiang, Wenbing; Huang, Yonghua
Abstract: Improvements in thermal insulation for cryogenic propellants tanks of rockets and spacecrafts are in high demand to meet the requirements for the tasks covering different phases from holding to launching and then to on-orbit. Embedding a vapor-cooled shield (VCS) in multi-layer insulation (MLI) blankets is one of the promising solutions. An experimental setup was designed and fabricated to investigate the correlating transient thermal behavior of both the cryogenic fluid inside the tank and the MLI-VCS composite insulation structure surrounding the tank. The effects of the filling rate and pressure control range on the temperature profiles, the heat flux, and the consequent mass loss rate were examined for the tanks equipped with or without the composite insulation structure. Results showed that the transient behavior of liquid flash boiling during the venting process has a significant impact on the fluid's pressure and temperature variation period, the tank's self-pressurization patterns as well as the mass loss rate. In addition, although the temperature of the VCS mildly fluctuated during the intermittent venting process, its effect of reducing heat leak is still encouraging. The measured daily evaporation rate can be reduced by 10.07% after introducing a VCS under the condition with the pressure control range of 462 ± 5 kPa and a liquid fill level of 51.8%. Highlights: A transient experimental setup was established for cryogenic insulation study. Effect of filling rate and pressure control range are discussed. VCS performs better at higher liquid filling rate. With VCS, narrower pressure control band leads to less of evaporation loss. Violent flash boiling increases the vented mass and prolongs the venting cycle.